LIVING LEARNING FROM NEAR DEATH EXPERIENCE - Veide, Mārtiņš (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The main aim of the article is to clarify what changes a near death experience (NDE) brings in the living learning process of an adult and in his attitude towards it. The existential experience, and the perceptions about life and death are considered as important self-realization and development factors in the learning process. Although currently there is no single scientific position with respect to NDE, the inner experience of the humans who have survived clinical death and as a result of that had personality change cannot be denied. In the context of pedagogy according to the phenomenological scientific methodological tradition NDE gives its contribution both in the procedure of cognition and in the field of the cognizable facts. In order to identify the relationship between NDE and living learning, in-depth interviews were conducted with 5 people who have experienced clinical death. The results of the interviews allow to identify several common change categories of the attitude and understanding related to living learning. These include the examination of one’s own way of existence, understanding of the unity of all existing, the appearance of a deeper sense of responsibility, new interests and the related intuitive knowledge, the change of attitude towards knowledge, religion and self-knowledge.